Computational analysis of the transportation phase of an innovative foundation for offshore wind turbine. (9th August 2021) - Cardoso, J.; Vieira, M.; Henriques, E.; Reis, L.
ABSTRACT: As the global demand for energy rises, renewable sources are increasingly becoming more accessible, and oceans show an excellent possibility for the expansion of wind energy. In this work, the structural integrity and the stability during the transportation of an innovative foundation for offshore wind turbines with self-floating capability are evaluated. The structure, with the turbine already installed, is transported to the installation site in its floating position assisted by towing vessels, being then submerged and fixed into the marine soil through suction piles. This paper focuses on the development of adequate numerical models to analyse the magnitude of the loadings subjected into the structure during transportation. FAST and AQWA are used to determine these aerodynamic and hydrodynamic loadings. The obtained results provide the necessary input data for the structural analysis using ANSYS to evaluate the stresses registered on the structure, as well as its vibration modes and stability.